Diabetic Ketoacidosis Caused by Acute Pancreatitis Results in Severe Hypertriglyceridemia: A Case Report - Amirpasha Mansour; Shima Ghasemzade (Clinical Medicine Insights: Endocrinology and Diabetes)
Diabetic ketoacidosis (DKA) is an acute complication of diabetes that mainly occurs in type 1 diabetes. However, it can also occur in type 2 diabetes, although less commonly. One of the rare causes of this condition is acute pancreatitis. While hypertriglyceridemia is a known complication of DKA, triglyceride levels higher than 2000 are an unusual finding. We present a case of undiagnosed type 2 diabetes mellitus in a patient who came to the hospital with epigastric pain, nausea, and vomiting. Subsequent blood tests revealed hyperglycemia, ketonuria, metabolic acidosis, and increased levels of amylase and lipase, leading to a simultaneous diagnosis of DKA, acute pancreatitis, and very severe hypertriglyceridemia. In patients experiencing abdominal pain and severe diabetic complications, acute pancreatitis should always be considered as a possible diagnosis, and triglyceride levels should be tested to identify hypertriglyceridemia as a potential cause of pancreatitis or complications of DKA.